Identification and characterization of histones in Physarum polycephalum evidence a phylogenetic vicinity of Mycetozoans to the animal kingdom. (17th November 2021) - Poulet, Axel; Mishra, Laxmi Narayan; Téletchéa, Stéphane; Hayes, Jeffrey J; Jacob, Yannick; Thiriet, Christophe; Duc, Céline
Abstract: Physarum polycephalum belongs to Mycetozoans, a phylogenetic clade apart from the animal, plant and fungus kingdoms. Histones are nuclear proteins involved in genome organization and regulation and are among the most evolutionary conserved proteins within eukaryotes. Therefore, this raises the question of their conservation in Physarum and the position of this organism within the eukaryotic phylogenic tree based on histone sequences. We carried out a comprehensive study of histones in Physarum polycephalum using genomic, transcriptomic and molecular data. Our results allowed to identify the different isoforms of the core histones H2A, H2B, H3 and H4 which exhibit strong conservation of amino acid residues previously identified as subject to post-translational modifications. Furthermore, we also identified the linker histone H1, the most divergent histone, and characterized a large number of its PTMs by mass spectrometry. We also performed an in-depth investigation of histone genes and transcript structures. Histone proteins are highly conserved in Physarum and their characterization will contribute to a better understanding of the polyphyletic Mycetozoan group. Our data reinforce that P. polycephalum is evolutionary closer to animals than plants and located at the crown of the eukaryotic tree. Our study provides new insights in the evolutionary history of Physarum and eukaryote lineages.